2015
DOI: 10.1002/jmv.24134
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus infections of the central nervous system: Laboratory diagnosis based on DNA detection by nested PCR in plasma and cerebrospinal fluid samples

Abstract: Infections of the central nervous systems (CNS) present a diagnostic problem for which an accurate laboratory diagnosis is essential. Invasive practices, such as cerebral biopsy, have been replaced by obtaining a polymerase chain reaction (PCR) diagnosis using cerebral spinal fluid (CSF) as a reference method. Tests on DNA extracted from plasma are noninvasive, thus avoiding all of the collateral effects and patient risks associated with CSF collection. This study aimed to determine whether plasma can replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Several in-vitro studies indicate that HHV-6 may activate EBV expression, which might promote EBV-associated diseases later in life [ 43 , 44 ]. A 2015 study reported two encephalitis cases with HHV-6 and EBV co-infection detected by PCR [ 45 ]. However, the coinfection of these two herpesviruses in our case cohort cannot be seen as causal agents of the astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several in-vitro studies indicate that HHV-6 may activate EBV expression, which might promote EBV-associated diseases later in life [ 43 , 44 ]. A 2015 study reported two encephalitis cases with HHV-6 and EBV co-infection detected by PCR [ 45 ]. However, the coinfection of these two herpesviruses in our case cohort cannot be seen as causal agents of the astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Rimerio et al reported the detection of infection with various herpesvirus strains in plasma and CSF using nested PCR. Notably, they found that the sensitivity of this method was low for HSV‐1 and EBV, and its positive predictive value (PPV) was low for HSV‐1 and HSV‐2 . Thus, low molecular detection sensitivity may be the main reason for the negative HSV DNA results from blood and CSF in our report.…”
Section: Discussionmentioning
confidence: 61%
“…The variations may be due to different groupings (which may include socioeconomic differences), the absence of active virus replication, or even methodological failure. HHV latency and the high serological prevalence found with this viral family do not reflect the active viral infection; therefore, the detection of latent particles can also influence the higher prevalence in some studies 2 , 3 , 21 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%